(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The physical working environment is the overall layout and design of the offices and workstations. Many physical work environment studies have shown workers are satisfied with specific workspace features. Numerous studies also have consistently demonstrated that characteristics of the physical work environment can significantly affect employees’ behavior, perceptions, and productivity. These features’ preferences by users are highly significant to their productivity and workspace satisfaction. Secondary data were collected and analyzed to achieve the study objective and for the purpose of this study. This study utilized the Pearson correlation coefficient to measure the statistical relationship between two variables. The independent variable is the physical work environment, including lighting, noise, temperature, office space/layout, and furniture design, while the dependent variable is the employees’ productivity. Moreover, the result of the hypothesis found that there is no significant relationship between the physical work environment and employees’ productivity. However, the researchers still recommended the management make some changes to their workplace to improve all the factors that this study used to improve employees’ productivity. In addition, researchers presented a pictorial layout plan for their workplace’s physical environment so that employees could remain productive at all times.